A novel, multidomain, primary care nurse-led and mHealth-assisted intervention for dementia risk reduction in middle-aged adults (HAPPI MIND): study protocol for a cluster randomised controlled trial - Amanda J Cross; Christine Walker; Kaarin J Anstey; Kevin Mc Namara; Vincent Versace; Parker Magin; Billie Bonevski; Amanda L Baker; Elizabeth Manias; J Simon Bell; Marlien Varnfield; Stephanie A Ward; et al. (BMJ Open)
Introduction Middle-aged multidomain risk reduction interventions targeting modifiable risk factors for dementia may delay or prevent a third of dementia cases in later life. We describe the protocol of a cluster randomised controlled trial (cRCT), HAPPI MIND (Holistic Approach in Primary care for PreventIng Memory Impairment aNd Dementia). HAPPI MIND will evaluate the efficacy of a multidomain, nurse-led, mHealth supported intervention for assessing dementia risk and reducing associated risk factors in middle-aged adults in the Australian primary care setting.Methods and analysis General practice clinics (n≥26) across Victoria and New South Wales, Australia, will be recruited and randomised. Practice nurses will be trained to implement the HAPPI MIND intervention or a brief intervention. Patients of participating practices aged 45–65 years with ≥2 potential dementia risk factors will be identified and recruited (approximately 15 patients/clinic). Brief intervention participants receive a personalised report outlining their risk factors for dementia based on Australian National University Alzheimer’s Disease Risk Index (ANU-ADRI) scores, education booklet and referral to their general practitioner as appropriate. HAPPI MIND participants receive the brief intervention as well as six individualised dementia risk reduction sessions with a nurse trained in motivational interviewing and principles of behaviour change, a personalised risk reduction action plan and access to the purpose-built HAPPI MIND smartphone app for risk factor self-management. Follow-up data collection will occur at 12, 24 and 36 months. Primary outcome is ANU-ADRI score change at 12 months from baseline. Secondary outcomes include change in cognition, quality of life and individual risk factors of dementia.Ethics and dissemination Project approved by Monash University Human Research Ethics Committee (ID: 28273). Results will be disseminated in peer-reviewed journals and at healthcare conferences. If effective in reducing dementia risk, the HAPPI MIND intervention could be integrated into primary care, scaled up nationally and sustained over time.Trial registration number ACTRN12621001168842.